2014
DOI: 10.1007/s11010-014-2011-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of NF2 gene mutations and pathogenesis-related proteins in sporadic vestibular schwannomas in young individuals

Abstract: Vestibular schwannomas (VSs) are benign tumors arising from eighth cranial nerve and most often occur sporadically in individuals of middle age group. Sporadic VSs are rarely reported in the young population. In this study, we evaluated clinical behaviors of 12 young sporadic VSs by the statistical comparison with a matched series of 145 adult cases. We found that young tumors were characterized by an earlier onset of initial symptom, shorter duration from the first symptom to diagnosis, and larger tumor size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…2D ) . As previously reported 79, 15, 19, 21 , most mutations identified were truncating mutations (nonsense, frameshift, and splicing-site mutations) throughout the first 15 exons of the gene. As shown in Table 2, most mutations occurred at the FERM domain of the NF2 protein (exon 1 to 8), but no particular mutational hot spots were found.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…2D ) . As previously reported 79, 15, 19, 21 , most mutations identified were truncating mutations (nonsense, frameshift, and splicing-site mutations) throughout the first 15 exons of the gene. As shown in Table 2, most mutations occurred at the FERM domain of the NF2 protein (exon 1 to 8), but no particular mutational hot spots were found.…”
Section: Resultssupporting
confidence: 68%
“…The “two-hits” inactivation of the NF2 gene that results in total merlin loss has also been demonstrated in sporadic VSs with detection rates ranging from 27% to 61% 711 , which is much less than expected. Additionally, conflicting results from merlin expression analyses have been reported in studies on sporadic VSs 1115 . They are classified by varying protein levels into none (or faint), medium or strong.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current treatment modalities include microsurgical removal and stereotactic radiosurgery, but complications from such interventions are not uncommon (Arthurs et al, 2011). Recently, several genes and pathways associated with VS, including NF2 (Chen et al, 2014), vascular endothelial growth factor A (VEGFA; Koutsimpelas et al, 2012;Dilwali et al, 2015), and PI3K/AKT (Jacob et al, 2008), have been identified. However, the molecular events involved in the development of this condition are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in NF2 have been identified not only in neurofibromatosis type 2-associated schwannoma, but also in sporadic unilateral VS (6,7). NF2 is located on chromosome 22q12, and although various mutation types, including nonsense, frameshift, missense, insertion, deletion and splice site mutations, have been detected, no mutational hot spots have been previously identified (3).…”
Section: Introductionmentioning
confidence: 99%